Efficacy of Combining Interview Techniques in Detecting Deception Related to Bio‐threat Issues. (18th February 2014) - Morgan, Charles A.; Rabinowitz, Yaron; Leidy, Robert; Coric, Vladimir; Busch, Kenneth G.; Schouten, Ronald; Weissman, Sidney H.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> The purpose of this project was to assess the detecting deception efficacy of three well‐validated "detecting deception" methods – i.e., forced choice testing (FCT), modified cognitive interviewing (MCI) and autobiographical implicit association testing (aIAT) – when applied to the issue of bio‐threat. The detecting deception accuracies of FCT and MCI were 81% and 75%, respectively. Although the aIAT mean response times in block 5 differed significantly between deceptive and truthful persons, the classification accuracy was low. FCT alone reduced the group of 64 persons to 11 and detected 50% of the liars; the false positive rate was 9%. MCI alone reduced the group of 64 to 24 and detected 92% of the liars; the false positive rate was 54%. When FCT was paired with MCI, 75% of liars were detected and the false positive rate was 13%. Forced choice testing and MCI show promise as methods for detecting deception related to bio‐threat under low‐base‐rate conditions. These methods took little time, enhanced the odds of detecting deceptive individuals and exhibited high positive likelihood ratios, suggesting that they have merit as screening tools. The aIAT required more time and was less accurate but may still serve as a useful screening tool. Copyright © 2014 John Wiley & Sons, Ltd.